EFFECT OF TA’AWUN (MUTUAL COOPERATION) AND SEJAHTERA LEADERSHIP ON SUSTAINING COMMUNITY ENGAGEMENT - Mhd Sarif, Suhaimi; Ismail, Yusof (Online Journal of Islamic Management and Finance (OJIMF), 2022)
This study explores the impact of ta’awun (mutual cooperation) and sejahtera (holistic) leadership. The scope is limited to 13 community engagement projects that were led by university students as part of their course assignments. There are two research objectives, namely (a) to investigate the effect of ta’awun and sejahtera leadership in aligning the community engagement projects with the course learning outcomes and 17 Sustainable Development Goals (SDGs) and, (b) to offer a model of ta’awun and sejahtera leadership in sustaining community engagement projects. The study applies qualitative research with constructionism paradigm through case study method. The study analysed the data with content analysis. Triangulation has been used to assure validity and reliability of the data. The key findings revealed that the effect of ta’awun and sejahtera leadership on coordination, facilitation, and maintenance of the community engagement projects. The practical application of the study is the integration of community engagement projects into university courses and assignments. This study is significant because it showcased the delivery of mutual benefits by the University stakeholders to the community. The future research should include industry engagement projects as well to integrate the industry and the university for greater ta’awun and sejahtera leadership.